1992
DOI: 10.1111/j.1471-4159.1992.tb10063.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of β‐Amyloid Protein Precursor and Microtubule‐Associated Protein τ During the Differentiation of Murine Embryonal Carcinoma Cells

Abstract: Expression of the genes encoding the beta/A4 amyloid protein precursor (APP) and microtubule-associated protein tau was studied in an embryonal carcinoma cell line (P19) that differentiates in vitro into cholinergic neurons after treatment with retinoic acid. Expression of APP increased 34- (mRNA) and 50-fold (protein) during neuronal differentiation; APP-695 accounted for most of this increase. These remarkable increases in APP expression coincided with a proliferation of neuronal processes and with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…3). This finding is in accord with the recent report of Fukuchi et al (43), who have similarly reported an up-regulation of JAPP in P19 cells upon RA-induced differentiation. We extended this analysis to primary hippocampal neurons, demonstrating that 3APP695 expression is also correlated with neuronal differentiation in a different cell culture paradigm (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…3). This finding is in accord with the recent report of Fukuchi et al (43), who have similarly reported an up-regulation of JAPP in P19 cells upon RA-induced differentiation. We extended this analysis to primary hippocampal neurons, demonstrating that 3APP695 expression is also correlated with neuronal differentiation in a different cell culture paradigm (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…pGEX-LRPC101 (4445-4544), coding for a fusion protein between GST and the 101 C-terminal residues of human low density lipoprotein receptor-related protein 1 (LRP), was PCR subcloned from pcDNA3.1-mLRP4T100, a gift from Dr. Guojun Bu (Washington University, St Louis). Constructs of pCA-APP695, pCA-S␤C, and pCA-APP⌬AICD were obtained from previous studies (30). All insert sequences were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…P1916 mouse embryonic carcinoma cells, and their clonal subline, P19 695B2 cells17, were cultured as described previously16. P19 and P19 695B2 cells were co‐transfected with pCA‐DI‐V and the hygromycin B phosphotransferase gene at a molar ratio of 10:1 using Lipofectamine (Life Technologies, Gaithersburg, MD, USA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%